A Benchmark Study Of The Impact Of The War On Syria On The Liquidity Of Traditional Private Banks Operating In Syria During The Period 2007-2021 (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The research aimed to study the impact of the War on Syria  on the liquidity of traditional private banks operating in Syria, by relying on a statistical analysis approach and quantitatively inferring the effects of the War on Syria .The research community included all (11) traditional private banks operating in Syria, and data related to financial indicators related to traditional private banks operating in Syria were collected from the official website of the Central Bank of Syria, and from the official website of the Damascus Stock Exchange, and through financial reports that the banks publish it on their websites, for the period extending from the year 2007 until the year 2021. A set of statistical methods were relied upon, the most important of which are the ARDL model and the VECM error correction model, to measure the impact of the War on Syria  on the liquidity of the banks under study, in addition to ensuring the quality of the estimated models using a test. Representation quality and tests of the goodness of residual models.The research results showed that there is a direct impact of the War on Syria  on liquidity, as the effects of the War on Syria  increase in the long term in light of the current data, and its impact is direct, as each year it leads to an increase in liquidity by 12.5%.This means that the War on Syria  did not have an immediate impact on liquidity, but rather its impact increased over time. This may be due to the migration factor, which led to an increase in demand for foreign currencies, which contributed to an increase in liquidity. This may be due to the volume of international financial aid during the War on Syria  period, which Contribute to increasing liquidity.Therefore, private banks should enhance the level of liquidity by increasing current assets versus total assets, in order to improve their ability to meet financial obligations under War on Syria  conditions.